2022
DOI: 10.1007/s11356-022-23535-2
|View full text |Cite
|
Sign up to set email alerts
|

The concentration of potentially toxic elements (PTEs) in drinking water from Shiraz, Iran: a health risk assessment of samples

Abstract: The existence of potentially toxic elements (PTEs) in water bodies has posed a menace to human health. Thus, water resources should be protected from PTEs, and their effect on the exposed population should be investigated. In the present investigation, the concentrations of PTEs such as lead (Pb), mercury (Hg), manganese (Mn), and iron(Fe) in the drinking water of Shiraz, Iran, were determined for the first time. In addition, hazard quotient, hazard index, cancer risk, and sensitivity analysis were applied to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…18 Furthermore, Amin's study on investigation of potentially toxic elements in drinking water revealed that Hg, Pb, Fe, and Mg showed there were not any harmful health risk for children and adults. 20 the carcinogenic and non-carcinogenic risk assessment of heavy metals in the water resources was conducted by Sadeghi. He concluded that the consumption of water endangered all consumer.…”
Section: Health Risk Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Furthermore, Amin's study on investigation of potentially toxic elements in drinking water revealed that Hg, Pb, Fe, and Mg showed there were not any harmful health risk for children and adults. 20 the carcinogenic and non-carcinogenic risk assessment of heavy metals in the water resources was conducted by Sadeghi. He concluded that the consumption of water endangered all consumer.…”
Section: Health Risk Assessmentmentioning
confidence: 99%
“…[14][15][16][17] While there have been several investigations into the contamination of drinking water with heavy metals through various studies, there is a lack of research specifically focused on health risk assessments related to backwash recovered from WTPs. [18][19][20] The quantitative chemical risk assessment (QCRA), hazard quotient (HQ), accumulation index, hazard index (HI), and quantitative microbial risk assessment (QMRA) are the main risk assessment methodologies that can be used for drinking water. Moreover, to investigate the amount of heavy metals in source water, the QCRA is a suitable index.…”
Section: Introductionmentioning
confidence: 99%